Cost-Effectiveness Analysis of Atezolizumab Versus Chemotherapy as First-Line Treatment for Metastatic Non-Small-Cell Lung Cancer With Different PD-L1 Expression Status - Liu, Guoqiang; Kang, Shuo; Wang, Xinchen; Shang, Fangjian (Frontiers in Oncology, 2021)
Background Atezolizumab could significantly improve clinical outcomes and was associated with less toxicity compared with chemotherapy as the first-line treatment of PD-L1-selected patients with EGFR and ALK wild-type metastatic non-small-cell lung cancer (NSCLC). However, the economic outcomes remain unclear yet in China. This study aimed to investigate the cost-effectiveness of atezolizumab versus chemotherapy as first-line therapy for metastatic NSCLC with different PD-L1 expression status from the Chinese health sector perspective. Methods A decision-analytic model was conducted to evaluate the economic outcomes for the first-line treatment of EGFR and ALK wild-type metastatic NSCLC with atezolizumab and chemotherapy in high PD-L1 expression, high or intermediate PD-L1 expression and any PD-L1 expression populations, respectively. The efficacy and safety data were obtained from the IMpower110 trial. Cost and utility values were gathered from the local charges and published literatures. Incremental cost-effectiveness ratio (ICER) was estimated. A scenario analysis for a patient assistance program (PAP) was conducted. One-way and probabilistic sensitivity analyses were performed to explore the robustness of the model results. Results Atezolizumab yielded additional 0.91 QALYs, 0.57 QALYs, 0.42 QALYs in comparison with chemotherapy, and the ICERs were 123,778.60/QALY, 142,827.19/QALY, 168,902.66/QALY in the high PD-L1 expression, high or intermediate PD-L1 expression, and any PD-L1 expression populations, respectively. When PAP was available, the ICERs were 52,414.63/QALY, 52,329.73/QALY, 61,189.66/QALY in the three categories of PD-L1 expression status populations, respectively. The ICERs were exceed the willingness-to-pay (WTP) threshold of 30,828/QALY (three times of per capita gross domestic product of China in 2019) in China. One-way sensitivity analyses suggested that the cost of atezolizumab played a vital role in the model outcomes, and the probabilistic sensitivity analyses showed atezolizumab was unlikely to be cost-effective at the WTP threshold regardless of PD-L1 expression status and whether the PAP was available or not. Conclusions Atezolizumab as first-line treatment for PD-L1-selected metastatic NSCLC patients without EGFR mutations or ALK translocations is unlikely to be cost-effective compared with chemotherapy regardless of PD-L1 expression status in the Chinese context.